Rainfall Estimation Using Specific Differential Phase for the First Operational Polarimetric Radar in Korea. (24th February 2014) - You, Cheol-Hwan; Lee, Dong-In; Kang, Mi-Young
Abstract : To assess the performance of rainfall estimation using specific differential phase observed by Bislsan radar, the first polarimetric radar in Korea, three rainfall cases occurring in 2011 were selected, each caused by different conditions: the first is the Changma front and typhoon, the second is only the Changma front, and the third is only a typhoon. For quantitative use of specific differential phase (K D P ), a data quality algorithm was developed for differential phase shift (Φ D P ), composed of two steps; the first involves removal of scattered noise and the second is unfolding of Φ D P . This order of the algorithm is necessary so as not to remove unfolded areas, which are the real meteorological target. All noise was removed and the folded Φ D P were unfolded successfully for this study. R K D P relations for S-band radar were calculated for 84, 754 samples of observed drop size distribution (DSD) using different drop shape assumptions. The relation for the Bringi drop shape showed the best statistics: 0.28 for normalized error, and 6.7 mm for root mean square error for rainfall heavier than 10 mm h - 1 . Because the drop shape assumption affects the accuracy of rainfall estimation differently for different rainfall types, such characteristics should be taken into account to estimate rainfall more accurately using polarimetric variables.